The Information Content of Equity Block Trades on the Warsaw Stock Exchange: An Estimation of Shares' Returns with the Usage of Simple Linear Regression and Multivariate Adaptive Regression Splines. (9th May 2014) - Kurek, Bartosz; Breitner, Michael H.; Dunis, Christian; von Mettenheim, Hans-Jörg; Neely, Christopher; Sermpinis, Georgios
ABSTRACT Equity block trade transactions per se directly relate to the valuation of a company's equity capital. These transactions are executed outside the continuous trading system and single price system, and involve trading of large volumes of shares at an agreed price. This paper investigates the information content of equity block trade transactions for companies constituting the WIG20 index from the Warsaw Stock Exchange in Poland. Two research methods are used: literature review and event study analysis. In the empirical part of the paper two approaches are used to model shares' returns: simple linear regression and multivariate adaptive regression splines. From the conducted research it is concluded that equity block trade transactions carry an important signal for investors acting on a stock exchange: significant abnormal positive (negative) returns follow the execution of the equity block trade, the price of which is higher (lower) than the closing price 2 days before the execution of the transaction. Copyright © 2014 John Wiley & Sons, Ltd.